A manual for design of hot mix asphalt with commentary (Report (National Cooperative Highway Research Program), 2011)
"TRB's National Cooperative Highway Research Program (NCHRP) Report 673: A Manual for Design of Hot-Mix Asphalt with Commentary incorporates the many advances in materials characterization and hot-mix asphalt (HMA) mix design technology developed since the conclusion of the Strategic Highway Research Program (SHRP). The final report on the project that developed NCHRP Report 673 and Appendixes C through F to NCHRP Report 673 were published as NCHRP Web-Only Document 159"--Publisher's description